1.4 kV Junction barrier Schottky rectifier with mixed trench structure. Issue 10 (1st October 2014) - Li‐kun, Xu; Ying, Wang; Zheng, Dou; Wei, Xue
Abstract : Junction barrier Schottky (JBS) rectifier with mixed trench structure on 4H‐SiC for improving the electrical performance is proposed. The device shows the increasing forward current density compared to the common JBS rectifier on 4H‐SiC because of the larger Schottky contact area without considerable degradation of breakdown voltage. This work is solely based on simulations with Silvaco TCAD tool. The forward current density of this device with 1.5 µm Schottky region depth of the trench structure is 102 A/cm 2 at the forward voltage drop of 3 V while the current density of the common JBS is 70 A/cm 2 . The proposed structure improves the forward voltage drop at 100 A/cm 2 effectively by 23%. The reverse characteristic and output capacitance of this device are similar to common JBS rectifier. In addition, in this work the forward and reverse characteristic of the proposed device at room and high temperatures is simulated.